New Strains of the Entomopathogenic Nematodes Steinernema scarabaei, S. glaseri, and S. cubanum for White Grub Management - Albrecht M. Koppenhöfer; Ana Luiza Sousa (Insects, 2024)
White grubs possess natural defense mechanisms against entomopathogenic nematodes (EPNs). Hence, EPN isolates that naturally infect white grubs tend to be among the most effective biological control agents of white grubs. We tested the virulence of four EPN isolates recently isolated from infected white grubs in turfgrass areas in central New Jersey, USA against third-instar larvae of Anomala orientalis, Popillia japonica, and Cyclocephala borealis, which are pests of turfgrass and ornamental plants in the northeastern USA. Against A. orientalis and P. japonica larvae, the Steinernema scarabaei Ad and S. scarabaei SL isolates were highly virulent in laboratory tests, whereas S. cubanum HF was less virulent and S. glaseri SH the least virulent. None of the isolates caused high mortality of C. borealis larvae. EPN efficacy in greenhouse tests against A. orientalis followed the same pattern. The original isolate of S. scarabaei, the AMK001 strain, that had been maintained in the laboratory on A. orientalis and P. japonica larvae for 19 years showed the same virulence level against A. orientalis larvae as it did soon after its first isolation and was also as virulent as the fresh S. scarabaei Ad isolate; both isolates were more virulent than S. scarabaei SL. Future tests should determine the ability of these white grub-adapted isolates to provide long-term suppression of white grub populations.